A rabbit osteochondral defect (OCD) model for evaluation of tissue engineered implants on their biosafety and efficacy in osteochondral repair - Zhou, Liangbin; Ho, Ki-Wai Kevin; Zheng, Lizhen; Xu, Jiankun; Chen, Ziyi; Ye, Xiangdong; Zou, Li; Li, Ye; Chang, Liang; Shao, Hongwei; Li, Xisheng; Long, Jing; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Osteochondral defect (OCD) is a common but challenging condition in orthopaedics that imposes huge socioeconomic burdens in our aging society. It is imperative to accelerate the R&D of regenerative scaffolds using osteochondral tissue engineering concepts. Yet, all innovative implant-based treatments require animal testing models to verify their feasibility, biosafety, and efficacy before proceeding to human trials. Rabbit models offer a more clinically relevant platform for studying OCD repair than smaller rodents, while being more cost-effective than large animal models. The core-decompression drilling technique to produce full-thickness distal medial femoral condyle defects in rabbits can mimic one of the trauma-relevant OCD models. This model is commonly used to evaluate the implant's biosafety and efficacy of osteochondral dual-lineage regeneration. In this article, we initially indicate the methodology and describe a minimally-invasive surgical protocol in a step-wise manner to generate a standard and reproducible rabbit OCD for scaffold implantation. Besides, we provide a detailed procedure for sample collection, processing, and evaluation by a series of subsequent standardized biochemical, radiological, biomechanical, and histological assessments. In conclusion, the well-established, easy-handling, reproducible, and reliable rabbit OCD model will play a pivotal role in translational research of osteochondral tissue engineering.